Examining the potential role of self-transcendence in the relationship between filial piety and meaning in life among Batak Toba young adults (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2025)
This study aims to investigate the mediating role of self-transcendence in the relationship between filial piety and life meaning among young Batak adults. Cultural values, such as Dalihan Na Tolu principle and filial piety, are believed to play a central role in shaping individuals' perceptions of life's meaning. This quantitative correlational study involved 151 young Batak adults aged 18–40 years, selected through purposive sampling. The instruments used include the Indonesian-adapted versions of the Portrait Values Questionnaire (PVQ-21), Dual Filial Piety Scale (DFPS), and Meaning in Life Questionnaire (MLQ). Mediation analysis revealed that self-transcendence did not serve as a significant mediator in the relationship between either reciprocal or authoritarian filial piety and meaning in life. However, a significant direct effect was found between authoritarian filial piety and meaning in life. These findings suggest that respect and obedience toward parents, as emphasized in authoritarian filial piety, positively contribute to the development of life meaning in the Batak cultural context. This study offers both theoretical and practical implications for understanding the importance of local cultural values in supporting psychological well-being, serving as a foundation for culturally sensitive interventions for young Batak Toba adults.